Multicomponent reactions involving arynes, quinolines, and aldehydes - Bhunia, Anup; Porwal, Digvijay; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
The multicomponent reaction involving arynes, quinolines, and aldehydes leading to the diastereoselective synthesis of benzoxazino quinoline derivatives in good yields proceeding via 1,4-zwitterionic intermediates is reported. In addition, the synthetic potential of various carbonyl compounds in this reaction as well as the utility of isoquinoline as the nucleophilic trigger has been examined.